Analisis Manajemen Risiko Menggunakan ISO 31000 pada Smart Canteen SMA XYZ - Dewangga Lazuardi Ramadhan; Ronie Febriansyah; Renny Sari Dewi (STMIK Budi Darma, 2020)
Risk is a danger, the consequences or consequences that can occur due to an ongoing process or a future event. Risk always confronts individuals and various institutions, including business organizations. In the business world, risk can be interpreted as an external or internal factor that can cause uncertainty in the effort to achieve the desired goals. Therefore, we need a management called risk management. Risk management is a process of identifying, analyzing, evaluating, controlling, and trying to avoid, minimize, or even eliminate unacceptable risks. In a company, risk management is a process of planning, organizing, directing and controlling the activities of an organization to minimize the risk of corporate revenue. The application of risk management usually uses ISO in accordance with risk analysis and the area to be focused. The stages of risk management analysis itself are, 1. Risk Collection, 2. Determining Scale, and 3. Risk Matrix. The results obtained from the risk management analysis will be in the form of suggestions, recommendations and mitigations.